TREN, BIAYA, DAN TANTANGAN STRUCTURAL HEALTH MONITORING JEMBATAN - Andreas A. Pramudya; Andreas Wibowo; Anton Soekiman (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2022)
Abstract Information technology and the Internet of Things are developing rapidly, resulting in changes in all fields, including monitoring and testing bridges. Structural Health Monitoring (SHM) is currently an alternative to replace conventional visual inspections. This study aims to determine trends in the use of Structural Health Monitoring on bridges, including cost factors and challenges faced, so that they can be considered and referenced in the installation of Structural Health Monitoring on bridges in the future. This study uses biblio-metric analysis methods and literature review. Bibliometric analysis was carried out to determine the type of bridge, the method of Structural Health Monitoring, the type of sensor, and the part that the sensor was installed on, so that the trend of Structural Health Monitoring installation could be observed. A literature review was carried out on the challenges that occurred and the cost factors that were considered and their potential in the future. This research shows that the method of Structural Health Monitoring is still evolving and that new technologies have been used to overcome various challenges, including the cost factor. If Structural Health Monitoring can be mass produced, the cost of producing Structural Health Monitoring is expected to decrease. Keywords: bridge; structural health monitoring; visual inspection; bibliometrics Abstrak Teknologi informasi dan Internet of Things berkembang dengan pesat, yang mengakibatkan terjadinya perubahan di segala bidang, termasuk pada pemantauan dan pengujian jembatan. Structural Health Monitoring (SHM) saat ini menjadi alternatif untuk menggantikan inspeksi visual yang bersifat konvensional. Penelitian ini bertujuan untuk mengetahui tren penggunaan Structural Health Monitoring pada jembatan, termasuk faktor biaya dan tantangan yang dihadapi, sehingga dapat menjadi pertimbangan dan acuan dalam pemasangan Structural Health Monitoring pada jembatan di masa mendatang. Studi ini menggunakan metode analisis bibliometrik dan tinjauan literatur. Analisis bibliometrik dilakukan untuk mengetahui jenis jembatan, metode Structural Health Monitoring, jenis sensor, dan bagian yang dipasang sensor, sehingga tren pemasangan Struc-tural Health Monitoring dapat diamati. Tinjauan literatur dilakukan pada tantangan yang terjadi dan faktor biaya yang menjadi pertimbangan serta potensinya di masa mendatang. Penelitian ini menunjukkan bahwa metode Structural Health Monitoring masih terus berkembang dan berbagai teknologi baru telah digunakan untuk mengatasi berbagai tantangan, termasuk faktor biaya. Jika Structural Health Monitoring dapat dipro-duksi secara massal, biaya produksi Structural Health Monitoring diharapkan menurun. Kata-kata kunci: jembatan; structural health monitoring; inspeksi visual; bibliometrik